2010
DOI: 10.1128/jb.00804-10
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity-Associated Islands in Extraintestinal PathogenicEscherichia coliAre Fitness Elements Involved in Intestinal Colonization

Abstract: The virulence of many human pathogens does not seem to be an evolutionarily selected trait, but an accidental by-product of the selection that operates in another ecological context. We investigated the possibility that virulence of the extraintestinal pathogenic Escherichia coli (ExPEC) strains, which frequently cause disease in the host in which they asymptomatically colonize the intestine, is the consequence of commensalism. Most of the ExPEC virulence factors are clustered on genomic islands called pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 61 publications
8
117
1
Order By: Relevance
“…The fact that these CTs belonged to pathogenic groups B2 and D and had the highest VAG scores suggests that certain E. coli clones of the dominant flora of the gut of healthy individuals are better equipped to cause UTI. Alternatively, these strains may be better adapted for the intestinal niche (Diard et al, 2010). Contrary to our expectation, we found that clones with increased virulence factors were more prevalent among elderly males than among young females.…”
Section: Phylogenetic Groupcontrasting
confidence: 56%
See 1 more Smart Citation
“…The fact that these CTs belonged to pathogenic groups B2 and D and had the highest VAG scores suggests that certain E. coli clones of the dominant flora of the gut of healthy individuals are better equipped to cause UTI. Alternatively, these strains may be better adapted for the intestinal niche (Diard et al, 2010). Contrary to our expectation, we found that clones with increased virulence factors were more prevalent among elderly males than among young females.…”
Section: Phylogenetic Groupcontrasting
confidence: 56%
“…Apart from their role in adhering to the urinary tract cells, P-pili have also been shown to bind to the intestinal tract, which enhances their colonization of the gut (Tullus et al, 1992;Wold et al, 1988Wold et al, , 1992. Pathogenicity-associated islands, which carry many extraintestinal virulence factors, have been shown to enhance fitness of these strains to survive in the intestinal tract, with the ability to cause extraintestinal infections being a coincidental by-product (Diard et al, 2010). Our unpublished data also indicate that E. coli strains carrying these adhesins bind with almost the same rate to Caco-2 cells (an intestinal epithelial cell line) as they do to the renal cell line A-489 (M. Katouli).…”
Section: Phylogenetic Groupmentioning
confidence: 99%
“…About 20% of all UTIs cases occur in men while 50-60% of women will have at least one episode of UTI during their lifetime (Griebling, 2005). There is a tendency of recurrence of UTIs in about 25-30% of women after the initial infection due to either re-infection or recrudescence (Bower et al, 2005) Escherichia coli can be broadly classified into three groups: commensal E. coli which constitute the normal floral of the intestine; intestinal pathogenic E. coli which causes various infections in the intestine and ExPEC which elicits infections in various parts of the body excluding the intestine (Diard et al, 2010). Extra-intestinal uropathogenic E. coli strains are defined as E. coli with enhanced ability to cause infections outside the intestinal tract, such as in the bloodstream, cerebrospinal fluid or urinary tract of the host (Diard et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is a tendency of recurrence of UTIs in about 25-30% of women after the initial infection due to either re-infection or recrudescence (Bower et al, 2005) Escherichia coli can be broadly classified into three groups: commensal E. coli which constitute the normal floral of the intestine; intestinal pathogenic E. coli which causes various infections in the intestine and ExPEC which elicits infections in various parts of the body excluding the intestine (Diard et al, 2010). Extra-intestinal uropathogenic E. coli strains are defined as E. coli with enhanced ability to cause infections outside the intestinal tract, such as in the bloodstream, cerebrospinal fluid or urinary tract of the host (Diard et al, 2010). Virulence factors associated with ExPEC include: adhesins, toxins (hemolysin and cytotoxic necrotizing factor), siderophores (aerobactin), host defense avoidance mechanisms/polysaccharides coatings (group II capsules and biofilm formation) and uropathogenic-specific protein (usp) (Arisoy et al, 2006;Skjøt-Rasmussen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Soto et al [47] reported that uropathogenic E. coli strains exposed to sub-inhibitory concentrations of quinolones showed partial or total loss of PAIs (pathogenicity islands) containing virulence factor genes. Diard et al's [48] findings that ExPEC PAIs play an important role in intestinal colonization and Moreno et al's [49] findings that group B2 and D tend to dominate fecal E. coli populations prior to extraintestinal infections suggest the presence of shared specific bacterial factors that contribute to fitness within the intestine. A striking finding from the present study is that 37% of group D ExPEC isolates and 23% of group B2 ExPEC isolates exhibited antibiotic resistance, and one ExPEC isolate from group B2 was resistant to all the antibiotics tested.…”
Section: Discussionmentioning
confidence: 99%